THE EFFECTIVENESS OF THE USE OF VILLAGE FUNDS IN THE IMPLEMENTATION OF DEVELOPMENT PROGRAMS IN EAST LOMBOK - Zohratul Aeni; Mila Maulana; Teni Susanti; Siti Raehan; Didin Hadi Saputra (EAJ (Economic and Accounting Journal), 2020)
The granting of regional autonomy to the broadest means the granting of authority and power (discretion) to the regions to manage and utilize regional resources optimally. In order to avoid irregularities and deviations, the granting of authority and broad powers must be followed by strong supervision. In this study, the authors used qualitative research methods. Qualitative research is research that is used to examine the condition of natural objects, as opposed to experiments, where the researcher is a key instrument, data collection techniques are carried out by triangulation (combined), descriptive data analysis and qualitative research results emphasize the meaning rather than generalization. In the research, researchers focus on the field of development in infrastructure development programs. Based on the results of research conducted by the author on the effectiveness of the use of village funds in the implementation of programs in the field of village development in Suralaga district, East Lombok regency in 2018, it can be measured using a target approach by looking at the outputs of activities, namely the realization of programs and the benefits of the programs classified as very effective.